O processo de avaliação psicológica na perspectiva da psicologia histórico cultural e suas contribuições para o processo de ensino-aprendizagem - Chiodi, Cinthia da Silva (2012)
From the moment that psychology has emerged as a science, until today, the psychometric tests are still widely used for the diagnosis of intellectual disabilities and learning disorders, especially in relation to the school. Thus, the evaluation process has always been tied to the responsibilities of a psychologist in the school, since the introduction of psychology in education.Today, with great emphasis given to studies and research in neuropsychology, one can observe the return to the use of standardized tests to measure the psychological functions. Thus, intelligence tests are still widely used in the diagnosis of intellectual disability as the assumption of success or failure of school children subjected to these assessment tools. Therefore, this research has the following objectives: at first, to analyze how, historically, a psychological evaluation has been developed in the school context, based mainly in psychometrics and in a second step, to understand how the psychological evaluation is being conducted by school psychologists in the State of Paraná. The research carried out we used a literature review and documentary research, this effected from the analysis of 36 reports of psychological evaluation performed for the referral of children from 5th to 8th grades of elementary school for the Resource Room. The literature is divided into two sections. The first section aims to discuss, briefly, on the development of psychological tests that had, since its inception until today, intended to measure intelligence. The second section aims to discuss the psychological assessment from a critical perspective of School Psychology. Finally, the third section will present the documentary research, which aims to identify which procedures are used by psychologists in the reports from referring students to the Resource Room. From the analysis of 36 reports, it was observed that most of the students assessed were in 5th and 6th grades, with the age of 12 and 13 years. It was observed that 33.3% of referrals for psychological assessment of the complaint were due to learning difficulties, although the reports do not always spell out what kind of difficulty the student had. The majority of opinions issued by psychologists, expressed as a classification of students with cognitive performance. 66.6% of the reports claim that the students had elowaverage performance expected for their chronological age and experience. As for the referral of students after the assessment, 50% of students were referred for psychotherapy, and 47.2% were referred for neurological assessment in relation to suggestions for working with students assessed, 61% of the reports had no suggestions for work with them. It was found that, in the State of Paraná, psychometrics is still quite strong, but it was also possible to note that some psychologists have mentioned that in addition to formal testing, other resources used during the evaluation process, demonstrating that assessments are not restricting only to psychometric tests. In general, we can say that there have been advances in the evaluation process in the literature and in the State of Parana, but much remains to be done in defense of access to all the knowledge produced by men in order to promote optimal development of potential students, especially in current times, when the medicalization has been a way found to solve the problems in the schooling process.